2021
DOI: 10.3389/fpls.2021.624442
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics of the “Arcanum” Species Group in Wild Tomatoes: Evidence for Separate Origins of Two Self-Compatible Lineages

Abstract: Given their diverse mating systems and recent divergence, wild tomatoes (Solanum section Lycopersicon) have become an attractive model system to study ecological divergence, the build-up of reproductive barriers, and the causes and consequences of the breakdown of self-incompatibility. Here we report on a lesser-studied group of species known as the “Arcanum” group, comprising the nominal species Solanum arcanum, Solanum chmielewskii, and Solanum neorickii. The latter two taxa are self-compatible but are thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…In addition to the four red/orange fruited tomato species, there are two additional SC species that group within a subclade known as the Arcanum group, which contains three species: SI S. arcanum , SC S. chmielewskii and SC S. neorickii . Recent data have shown that while both SC species are derived from SI S. arcanum , they are independently derived from distinct geographical subsets of S. arcanum ( Florez-Rueda et al, 2021 ). The single known S-RNase allele in S. chmielewskii , LcwSRN-1 (after the previous species name, Lycopersicum chmielewskii ), is not expressed at the RNA level ( Kondo et al, 2002a ), and the transition from SI to SC in S. chmielewskii likely followed the typical pistil first pattern with a loss of S-RNase function ( Markova et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the four red/orange fruited tomato species, there are two additional SC species that group within a subclade known as the Arcanum group, which contains three species: SI S. arcanum , SC S. chmielewskii and SC S. neorickii . Recent data have shown that while both SC species are derived from SI S. arcanum , they are independently derived from distinct geographical subsets of S. arcanum ( Florez-Rueda et al, 2021 ). The single known S-RNase allele in S. chmielewskii , LcwSRN-1 (after the previous species name, Lycopersicum chmielewskii ), is not expressed at the RNA level ( Kondo et al, 2002a ), and the transition from SI to SC in S. chmielewskii likely followed the typical pistil first pattern with a loss of S-RNase function ( Markova et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hanneman, 1980, 1982;Dinu et al, 2005); Div: (Särkinen et al, 2013;Fumia, 2021;Tang et al, 2022) Solanum sect. Lycopersicon celluar several instances; often complete or strongly asymmetric crown age ~1.2-2.6MY, incidences in species pairs <1MY diverged Both (Rick, 1963;Ehlenfeldt and Hanneman, 1992;Ehlenfeldt and Ortiz, 1995;Baek et al, 2016;Roth et al, 2018a;Florez-Rueda et al, 2021b)Div: (Särkinen et al, 2013;Pease et al, 2016) Brassica nuclear several instances; often strong earliest incidences between species ~2MY diverged Both (Nishiyama et al, 1991); Div: (Li et al, 2017) Nicotiana celluar several instances; often complete or strongly asymmetric crown age ~10-13MYA; few crosses made between recently diverged species Both (McCray, 1932;East, 1935;Cooper and Brink, 1940); Div (Clarkson et al, 2017; Triticum nuclear strong HSI between T. boeoticum and T. urartu ~1MY divergd Both (Gill and Waines, 1978); Div (Huynh et al, 2019) Aegilops nuclear strong HSI between Ae. tauschii (Ae.…”
Section: Increased Expression Of the Peg (Orange) Selects For Increas...mentioning
confidence: 99%
“…The SI of tomatoes is of an S-RNase type which is characteristic of Solanaceae [10]. The study of SI in tomatoes has been ongoing for a long time [17] and is still in progress [18][19][20]. Tomatoes are a popular object in the studies of SI evolution and variation in the S locus [18,21,22].…”
Section: Introductionmentioning
confidence: 99%